Alternatives to Invasive Plants Commonly Found in Central Florida Landscapes - Gary W. Knox; Sandra B. Wilson; Zhanao Deng; Rosanna Freyre (EDIS)
Based on years of UF/IFAS research producing and trialing cultivars, this 3-page fact sheet lists native and non-invasive, non-native ornamentals as alternatives to invasive plants commonly used in Central Florida landscapes. Only plants considered to be generally available in the nursery trade are listed. Alternative plants are similar to respective invasive plants as much as possible in terms of size, habit, texture, and flower color. This 3-page fact sheet was written by Gary W. Knox, Sandra B. Wilson, Zhanao Deng, and Rosanna Freyre, and published by the UF Department of Environmental Horticulture, August 2013.